Police legitimacy and approval of vigilante violence: The significance of anger - Asif, Muhammad (Theoretical criminology, 2023)
Most of the previous studies on vigilante violence suggest that people employ vigilante violence instrumentally to compensate for a lack of state monopoly on violence and the state's illegitimacy in controlling crime. This study, however, highlights the significance of emotions—most notably anger—in explaining approval of vigilante violence. A cross-sectional study was conducted at six Pakistani universities with a sample of 500 students recruited through online surveys. The results of the regression models show that police legitimacy and trait anger independently predict approval of vigilante violence both directly and indirectly via righteous anger. Thus, the findings suggest that people who are easily angered and who perceive the police as corrupt and procedurally unjust feel righteous anger and are likely to approve of vigilante violence.